The Role of Information Technology Education in Improving Human Resource Quality in the Technology Sector - Padjri Agustino; Ahmad Ridoh; Yogi Irdes Putra (Jurnal Ilmiah Global Education, 2026)
The rapid development of information technology requires human resources (HR) who are adaptive, competent, and competitive. This study analyzes the role of information technology education in improving HR quality in the technology sector through a systematic literature review of Indonesian studies. The findings show that IT education, in both formal settings (schools and universities) and non-formal programs (courses, certifications, and industry-based training), significantly enhances technical skills such as programming, cybersecurity, and data analysis, while also developing non-technical skills like communication, collaboration, and problem-solving. Technology-based learning models, including e-learning, blended learning, and project-based learning, have proven to expand access, increase effectiveness, and foster innovation in learning. Collaboration between educational institutions, industry, and government is essential to align curricula with workforce needs. Despite challenges such as limited infrastructure, unequal internet access, and varying educator capacities, the study confirms that investing in IT education is a strategic approach to developing high quality human resources and supporting national competitiveness in the digital era.